2015 Indicators of Regulatory Policy and Governance Design, Methodology and Key Results - Arndt, Christiane (OECD Regulatory Policy Working Papers, 2015)
This paper presents the methodology, key results and statistical analysis of the 2015 Indicators for Regulatory Policy Governance (iREG) to complement the OECD Regulatory Policy Outlook 2015. Three composite indicators were constructed corresponding to three key principles of the 2012 OECD Recommendation of the Council on Regulatory Policy and Governance: Regulatory Impact Assessment; stakeholder engagement; and ex post evaluation. This paper explains the process by which the indicators were developed, presents main results, and outcomes of different sensitivity analyses that were performed to test the robustness of the methodology, including principal components analysis, Monte Carlo analysis and weight-sensitivity analysis